Investigation of the Consequences of Mounting Laying Defects for Curved Surface Slider Devices under General Seismic Input. Issue 3 (16th March 2019) - Pavese, A.; Furinghetti, M.; Casarotti, C.
ABSTRACT: Experimental studies performed on friction-based isolators have shown widely sparse frictional response, as direct effect of intrinsic properties of the devices and the vertical load variation. Moreover, in practical applications mounting laying defects consisting of uneven inclinations of the sliding surfaces with respect to the horizontal plane have been recognized as a potential cause of deviation from the response assumed in the design phase. In this paper mono and biaxial motions of a base-isolated RC building have been investigated; the aim of the work is to identify the effects of both laying defects and friction variation on the seismic response.